Electrospray ionization deposition of ultrathin ionic liquid films: [C 8C1Im]Cl and [C8C1Im][Tf 2N] on Au(111) - Rietzler, Florian; Piermaier, Marius; Deyko, Alexey; Steinrück, Hans-Peter; Maier, Florian (Langmuir, 2014)
We introduce a new method for preparing ultrathin ionic liquid (IL) films on surfaces by means of electrospray ionization deposition (ESID) under ultraclean and well-defined ultra-high-vacuum (UHV) conditions. In contrast to physical vapor deposition (PVD) of ILs under UHV, ESID even allows deposition of ILs, which are prone to thermal decomposition. As proof of concept, we first investigated ultrathin [CCIm][TfN] (=1-methyl-3-octyl imidazolium bis(trifluoromethyl)imide) films on Au(111) by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Films obtained by ESID are found to be virtually identical to films grown by standard PVD. Thereafter, ESID of [CCIm]Cl on Au(111) was studied as a first example of an IL that cannot be prepared as ultrathin film otherwise. [C CIm]Cl forms a wetting layer with a checkerboard arrangement with the cationic imidazolium ring and the chloride anion adsorbed next to each other on the substrate and the alkyl chain pointing toward vacuum. This arrangement within the wetting layer is similar to that observed for [CCIm][TfN], albeit with a higher degree of order of the alkyl chains. Further deposition of [CC Im]Cl leads to a pronounced island growth on top of the wetting layer, which is independently confirmed by ARXPS and atomic force microscopy. This behavior contrasts the growth behavior found for [CC Im][TfN], where layer-by-layer growth on top of the wetting layer is observed. The dramatic difference between both ILs is attributed to differences in the cation-anion interactions and in the degree of order in the wetting layer of the two ILs. © 2014 American Chemical Society.

Influence of substituents and functional groups on the surface composition of ionic liquids - Kolbeck, Claudia; Niedermaier, Inga; Deyko, Alexey; Lovelock, Kevin; Taccardi, Nicola; Wei, Wei; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2014)
We have performed a systematic study addressing the surface behavior of a variety of functionalized and non-functionalized ionic liquids (ILs). From angle-resolved X-ray photoelectron spectroscopy, detailed conclusions on the surface enrichment of the functional groups and the molecular orientation of the cations and anions is derived. The systems include imidazolium-based ILs methylated at the C2 position, a phenyl-functionalized IL, an alkoxysilane-functionalized IL, halo-functionalized ILs, thioether- functionalized ILs, and amine-functionalized ILs. The results are compared with the results for corresponding non-functionalized ILs where available. Generally, enrichment of the functional group at the surface is only observed for systems that have very weak interaction between the functional group and the ionic head groups. Scratching the surface: The surface behavior of various functionalized ionic liquids (ILs) is studied by angle-resolved X-ray photoelectron spectroscopy and conclusions on surface-enrichment effects and molecular orientation of cations and anions are derived (see figure; Im=imidazolium, Tf=trifluoromethanesulfonyl). Overall, surface enrichment is only observed for functional groups that interact weakly with the ionic head groups. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Interface properties and physicochemical characterization of the low-temperature molten salt Li/K/Cs acetate - Deyko, Alexey; Bajus, Stephanie; Rietzler, Florian; Bösmann, Andreas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2013)
The surface of macroscopic films of the ternary molten salt mixture Li KCs[OAc] has been investigated by angle-resolved X-ray photoelectron spectroscopy (XPS) as a function of temperature. With increasing temperature a preferential depletion of K is observed by ∼40%. From temperature programmed desorption we find that the onset for the cation desorption follows the order Cs, K, and Li, with activation energies of 125, 148, and 157 kJ mol, respectively; the corresponding value for the [OAc] anion is 147 kJ mol, which is, within the margin of error, identical to the average of the value found for the cations. Ultrathin films of the molten salt deposited on a Au(111) surface by physical vapor deposition show preferential enrichment of Cs, in line with the lower activation energy and thus higher desorption rate of Cs[OAc] from the ternary mixture. Angle-resolved XPS of the molten salt/gold interface demonstrates that the first molten salt monolayer grows in a layer-by-layer growth, followed by three-dimensional island growth at higher coverages. © 2013 American Chemical Society.

Interfaces of ionic liquids and transition metal surfaces - Adsorption, growth, and thermal reactions of ultrathin [C 1C 1Im] [Tf 2N] films on metallic and oxidised Ni(111) surfaces - Cremer, Till; Wibmer, Leonie; Krick Calderon, Sandra; Deyko, Alexey; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2012)
Ultrathin films of the ionic liquid 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C C Im][Tf N]) were deposited on differently terminated Ni(111) single crystal surfaces. The initial wetting behaviour, the growth characteristics, the molecular arrangement at the interface, and thermal reactivity were investigated using angle-resolved X-ray photoelectron spectroscopy (ARXPS). On clean Ni(111), the initial growth occurs in a layer-by-layer mode. At submonolayer coverages up to at least 0.40 ML, a preferential arrangement of the IL ions in a bilayer structure, with the imidazolium cations in contact with the Ni surface atoms and the anions on top of the cation, is deduced. For higher coverages, a transition to a checkerboard-type arrangement occurs, which is most likely due to repulsive dipole-dipole interactions in the first layer. An overall preference for a checkerboard-type adsorption behaviour, i.e., anions and cations adsorbing next to each other, is found on the oxygen-precovered O(√3×√3)R30°Ni(111) surface. The thermal stability of adsorbed IL layers on Ni(111) and on a fully oxidised Ni(111) surface was studied by heating the layers to elevated temperatures. For clean Ni(111) reversible adsorption takes place. For the oxidised surface, however, only cation-related moieties desorb, starting at ∼450 K, while anion-related signals remain on the surface up to much higher temperatures. © 2012 the Owner Societies.

Interfacial behavior of thin ionic liquid films on mica - Deyko, Alexey; Cremer, Till; Rietzler, Florian; Perkin, Susan; Crowhurst, Lorna; Welton, Tom; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2013)
Ultrathin films of two imidazolium-based ionic liquids (ILs), [C CIm][TfN] (=1-methyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) and [CCIm][Tf N] (=1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) were deposited on mica surfaces by physical vapor deposition in ultrahigh vacuum. Using angle-resolved X-ray photoelectron spectroscopy (ARXPS), the initial wetting behavior, the growth characteristics, and the molecular arrangement of the ions at the interface were investigated. The measurements were performed on freshly air-cleaved mica surfaces with different carbon precoverages. ARXPS clearly reveals that the initial IL adsorption behavior strongly depends on the amount of preadsorbed carbon: On clean mica, 3D growth (complete dewetting) occurs, whereas on a fully carbon covered surface, initially a complete 2D wetting layer forms, followed by 3D growth. © 2013 American Chemical Society.

Liquid/solid interface of ultrathin ionic liquid films: [C 1C1Im][Tf2N] and [C8C 1Im][Tf2N] on Au(111) - Cremer, Till; Stark, Michael Werner; Deyko, Alexey; Steinrück, Hans-Peter; Maier, Florian (Langmuir, 2011)
Ultrathin films of two imidazolium-based ionic liquids (IL), [C CIm][TfN] (= 1,3-dimethylimidazolium bis(trifluoromethyl)imide) and [CCIm][TfN] (= 1-methyl-3-octylimidazolium bis(trifluoromethyl)imide) were prepared on a Au(111) single-crystal surface by physical vapor deposition in ultrahigh vacuum. The adsorption behavior, orientation, and growth were monitored via angle-resolved X-ray photoelectron spectroscopy (ARXPS). Coverage-dependent chemical shifts of the IL-derived core levels indicate that for both ILs the first layer is formed from anions and cations directly in contact with the Au surface in a checkerboard arrangement and that for [CC Im][TfN] a reorientation of the alkyl chain with increasing coverage is found. For both ILs, geometry models of the first adsorption layer are proposed. For higher coverages, both ILs grow in a layer-by-layer fashion up to thicknesses of at least 9 nm (>10 ML). Moreover, beam damage effects are discussed, which are mainly related to the decomposition of [TfN] anions directly adsorbed at the gold surface. © 2011 American Chemical Society.

Low melting Li/K/Cs acetate salt mixtures as new ionic media for catalytic applications - first physico-chemical characterization - Bajus, Stephanie; Deyko, Alexey; Bösmann, Andreas; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Dalton Transactions, 2012)
In order to expand the temperature limits of Supported Ionic Liquid Phase (SILP) or Solid Catalyst with Ionic Liquid Layer (SCILL) systems to higher operation temperatures, the mixture of lithium acetate, potassium acetate, and caesium acetate (molar ratio of 0.2/0.275/0.525) has been studied in detail. Physico-chemical properties of the bulk melt are reported together with stability data of the modern salt on various solid support materials showing attractive properties for many potential high temperature applications. © 2012 The Royal Society of Chemistry.

Temperature-dependent surface-enrichment effects of imidazolium-based ionic liquids - Kolbeck, Claudia; Deyko, Alexey; Matsuda, Takashi; Kohler, Florian; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2013)
We present the first systematic study of the influence of temperature on the degree of surface enrichment of 1-alkyl-3-methylimidazolium-based ionic liquids (ILs). Using angle-resolved X-ray photoelectron spectroscopy, we demonstrate that the degree of surface enrichment strongly decreases with increasing temperature for all the studied ILs. For ILs with the same cation, but different anions, [CCIm]Br, [CC Im][TfO] and [CCIm][TfN], no significant differences of the temperature-induced partial loss of surface enrichment are found. Measurements for [CCIm][TfO], [CCIm][TfO] and [CCIm][TfO] indicate a small effect of the chain length. For [CC Im][TfO], a continuous decrease of alkyl surface enrichment is found with increasing temperature, with no abrupt changes at the phase-transition temperature from the smectic A to the isotropic phase, indicating that the surface enrichment is not affected by this phase transition. Loss of order! The surface enrichment of the alkyl chains of five imidazolium-based ionic liquids (ILs) at the liquid/vacuum interface is studied as a function of temperature by angle-resolved X-ray photoelectron spectroscopy; both the anion and the alkyl chain length at the cation are varied. At room temperature, the alkyl chains are enriched at the outer surface. Upon increasing the temperature, the degree of surface enrichment decreases. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.